(untitled) (INTERNATIONAL CONFERENCE OF NATURAL AND SOCIAL-HUMANITARIAN SCIENCES, 2025)
Before the Shaybanid state established its rule in the oases between the Amu Darya and Syrdarya rivers, including the Jizzakh oasis, the main political and ethnic processes associated with the Shaybanid dynasty took place in the eastern part of the Dashti-Kipchak - the middle and lower basins of the Syrdarya, the Urals, Western Siberia and Balkhash. The tribes and peoples living in these regions, such as the "Kung’irat", "Man’it", "Naiman", "Burgut", "Qarluq", and "Boyrak", played a significant role in the political activities of Genghis’ rulers.